2011
DOI: 10.1097/prs.0b013e31820cf5c6
|View full text |Cite
|
Sign up to set email alerts
|

Lambda-Shaped Anastomosis with Intravascular Stenting Method for Safe and Effective Lymphaticovenular Anastomosis

Abstract: Lambda-shaped anastomosis assisted by intravascular stenting is a safe and relatively easy method that can be performed by surgeons with less than 1 year of experience in microsurgery. This in turn allows efficient lymphaticovenular anastomoses to be performed simultaneously by a team of surgeons, resulting in an increased number of bypasses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
174
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 143 publications
(176 citation statements)
references
References 18 publications
1
174
0
Order By: Relevance
“…1Y9 In LVA, Yamamoto et al 8 have reported that making bypasses with not only the distal end of a lymphatic vessel but also the proximal end would lead to a better prognosis. This is because retrograde proximalto-distal lymph flow is often observed in lymphedema patients, probably the result of impaired valves in the lymphatic vessel.…”
Section: Discussionmentioning
confidence: 99%
“…1Y9 In LVA, Yamamoto et al 8 have reported that making bypasses with not only the distal end of a lymphatic vessel but also the proximal end would lead to a better prognosis. This is because retrograde proximalto-distal lymph flow is often observed in lymphedema patients, probably the result of impaired valves in the lymphatic vessel.…”
Section: Discussionmentioning
confidence: 99%
“…Then we decide which approach to use depending on the position and size of recipient vein. 1,2,4,5 When sclerosis is severe, on the other hand, a SeE or SeS technique is not appropriate because of the difficulty to create a window on a lymphatic vessel. In such a case, an EeE or EeS LVA is a method of choice and we select one of them depending on the position and size of recipient vein.…”
Section: Dear Sirmentioning
confidence: 97%
“…In such a case, an EeE or EeS LVA is a method of choice and we select one of them depending on the position and size of recipient vein. 1,2,4 It is important for a surgeon to choose anastomotic configurations suited for the condition of the vessels for maximization of the number of LVAs in a surgical field. 6,7 Figure 1 All-star lymphaticovenular anastomosis.…”
Section: Dear Sirmentioning
confidence: 99%
“…Supermicrosurgery (anastomosis less than 0.8 mm vessels) is used in this technique, in which lymphatic vessels and adjacent venules are anastomosed, mostly in an end-to-end fashion (39,43) (Figure 5). Variations on the configuration of anastomosis type were described in several studies with variable success rates (45,46). Studies have reported improvement in patients both subjectively and objectively.…”
Section: Physiologic Techniquesmentioning
confidence: 99%